Joint association of dietary live microbe intake and depression with cancer survivor in US adults: evidence from NHANES - Dekui Jin; Tian Lv; Chengying Zhang; Yi Hu (BMC Cancer)
Abstract Background The mortality of cancer survivors is influenced by various factors. This study aims to investigate the relationship between dietary live microbe intake and depression with the mortality of cancer survivors among U.S. adults. Methods This cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning from 2001 to 2018. Based on the classification by Sanders et al., foods were categorized by their levels of live microbes as follows: low (< 10^4 CFU/g), medium (10^4–10^7 CFU/g), and high (> 10^7 CFU/g). Using this classification and dietary questionnaire data, participants were divided into three groups: (1) low dietary live microbe intake (only low-level foods), (2) medium dietary live microbe intake (medium but not high-level foods), and (3) high dietary live microbe intake (any high-level foods). Additionally, foods classified as medium and high were combined into a “Medium-High” category. Cancer survivors were identified by their affirmative response to the question: “Have you ever been told by a doctor or other health professional that you had cancer or malignancy of any kind?” The Patient Health Questionnaire-9 (PHQ-9) was administered to assess depressive symptoms, with a score of ≥ 10 indicating depression. The study examined the independent and joint associations of dietary live microbe intake and depression with mortality outcomes in cancer survivors, employing Cox regression analysis adjusted for weights to calculate relative risk. Mediation analysis was conducted to evaluate the effect of PHQ-9 on the relationship between dietary live microbe intake and all-cause mortality in cancer patients. Results During a median follow-up of 6.2 years, we identified a total of 605 all-cause mortality among participants, including 204 from cancer and 401 from non-cancer-related causes. The analysis showed that medium-high dietary live microbe intake was consistently associated with a lower risk of all-cause mortality (HR, 0.741; 95% CI, 0.602–0.912; P = 0.005) and non-CVD mortality (HR, 0.687; 95% CI, 0.545–0.866; P = 0.001) when compared to low dietary live microbe intake in adjusted models. Conversely, depression was linked to a higher risk of all-cause mortality (HR, 1.789; 95% CI, 1.281–2.473; P < 0.001) and non-CVD mortality (HR, 1.901; 95% CI, 1.249–2.793; P = 0.001) compared to individuals without depression. Notably, joint analyses revealed that low dietary live microbe intake was associated with the highest risk of all-cause mortality among cancer survivors who also experienced depression (HR, 3.122; 95% CI, 1.734–5.619; P <  0.001). Additionally, mediation analysis indicated that the PHQ-9 score mediated 18.4% of the association between dietary live microbe intake and all-cause mortality in cancer survivors mediation proportion 18.4%; 95% CI, 7.5-29.2%. Conclusions Our results indicated that low dietary live microbe intake and depression are associated with an increased risk of non-CVD and all-cause mortality among cancer survivors. Additionally, the PHQ-9 score demonstrated a mediating effect on the relationship between dietary live microbe intake and all-cause mortality in this population.